Magnetic alignment device for negative electrodes and method for manufacturing negative electrodes using the same

JP2025504761AActive Publication Date: 2025-02-19LG ENERGY SOLUTION LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024539358
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-09-15
Filing Date
2023-09-13
Publication Date
2025-02-19
Estimated Expiration
2043-09-13

AI Technical Summary

Benefits of technology

【0025】 本発明に係る磁性整列装置は、負極集電体上に塗布された負極スラリーのローディング量をリアルタイムで測定し得、このように測定された負極スラリーのローディング量に応じて、磁石部の磁石列を構成する単位磁石の離隔距離を個別に調節して磁場の強度を容易に制御し得るので、製造された負極活性層に含有された炭素系負極活物質の結晶面の整列度が均一に高いという利点がある。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025504761000001_ABST
    Figure 2025504761000001_ABST
Patent Text Reader

Abstract

The present invention relates to a magnetic alignment device used in manufacturing a negative electrode and a method for manufacturing a negative electrode using the same. The magnetic alignment device measures the loading amount of a negative electrode slurry applied to a negative electrode current collector in real time, and can easily control the strength of a magnetic field by adjusting the separation distance of a magnet part according to the measured loading amount of the negative electrode slurry, which is advantageous in that the degree of alignment of the crystal plane of a carbon-based negative electrode active material contained in a manufactured negative electrode active layer is uniformly high.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0116184 dated September 15, 2022, and all contents disclosed in the documents of said Korean patent application are incorporated herein by reference.

[0002] The present invention relates to a magnetic alignment device capable of uniformly aligning anode active material in anode active layer during anode production, and a method for producing anode using the same. [Background technology]

[0003] 2. Description of the Related Art In recent years, secondary batteries have been widely used not only in small devices such as portable electronic devices, but also in medium- to large-sized devices such as battery packs for hybrid and electric vehicles and power storage devices.

[0004] Such secondary batteries are power generating elements capable of being charged and discharged and have a laminated structure of a positive electrode / separator / negative electrode. In general, the positive electrode contains a lithium metal oxide as a positive electrode active material, and the negative electrode contains a carbon-based negative electrode active material such as graphite. During charging, lithium ions released from the positive electrode are absorbed into the carbon-based negative electrode active material of the negative electrode, and during discharging, the lithium ions contained in the carbon-based negative electrode active material are absorbed into the lithium metal oxide of the positive electrode, thereby allowing repeated charging and discharging.

[0005] In this case, examples of the negative electrode active material used in the negative electrode include graphite materials such as natural graphite. Such graphite has a layered structure, in which carbon atoms form a network structure, and many layers that spread out in a planar shape are stacked. During charging, lithium ions penetrate from the edge faces (surfaces where layers overlap) of such graphite layers and diffuse between the layers. During discharging, lithium ions can be desorbed and released from the edge faces of the layers. In addition, since the electrical resistivity of graphite in the plane direction of the layers is lower than that in the stacking direction of the layers, a detouring electron conduction path is formed along the plane direction of the layers.

[0006] In this regard, a technique has been proposed for magnetically orienting the graphite contained in the negative electrode in order to improve the charging performance of the negative electrode in conventional lithium secondary batteries using graphite. Specifically, the (002) crystal plane of the graphite is oriented in a magnetic field during the formation of the negative electrode so that it is nearly perpendicular to the negative electrode current collector, and then fixed. In this case, the edge face of the graphite layer faces the positive electrode active layer, so that the insertion and desorption of lithium ions is smooth, and at the same time, the electron conduction path is shortened, improving the electronic conductivity of the negative electrode, thereby improving the charging performance of the battery.

[0007] However, although a magnetic field can be applied to undried negative electrode slurry to induce the orientation of graphite, the conditions of the applied magnetic field may vary depending on various variables such as the loading amount and thickness of the negative electrode slurry containing graphite. However, there is a limitation in that it is difficult to reflect such variables in real time during actual negative electrode manufacturing, and therefore there is a problem in that it is difficult to realize uniform orientation of graphite.

[0008] In addition, a single negative electrode manufacturing apparatus will produce a variety of models of negative electrodes with different specifications, and it is not easy to control the magnetic field application means, i.e., permanent magnets, etc., provided in the manufacturing apparatus according to the specifications of the negative electrodes being manufactured.

[0009] Therefore, there is a need for a technology that can easily control a magnetic field application means according to the specifications of the negative electrode to be manufactured, such as the loading amount and thickness of the negative electrode active layer, and / or the negative electrode manufacturing conditions, such as the loading amount of the negative electrode slurry, and can manufacture a negative electrode active layer in which the crystal planes of the carbon-based negative electrode active material, such as graphite, are uniformly aligned. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Korean Patent Publication No. 10-2018-0048131 [Patent Document 2] Korean Patent Publication No. 10-2022-0060017 Summary of the Invention [Problem to be solved by the invention]

[0011] An object of the present invention is to provide an alignment device capable of uniformly aligning crystal planes of a carbon-based negative electrode active material contained in a negative electrode active layer by adjusting the strength of a magnetic field according to the loading amount of a negative electrode slurry containing a carbon-based negative electrode active material, and a method for manufacturing a negative electrode using the same. [Means for solving the problem]

[0012] In order to solve the above-mentioned problems, in one embodiment, the present invention comprises: A magnetic alignment device for a negative electrode, which applies a magnetic force to a negative electrode sheet in which a negative electrode slurry containing a carbon-based negative electrode active material is applied onto a negative electrode current collector, thereby orienting the carbon-based negative electrode active material, a first magnet portion and a second magnet portion respectively disposed above and below the traveling electrode sheet; a loading amount measuring unit that is disposed upstream of the first magnet unit and the second magnet unit with respect to the running direction of the electrode sheet and that measures a loading amount of the negative electrode slurry disposed on the electrode sheet; a control unit that adjusts a distance between the first magnet unit and the second magnet unit according to a loading amount of the negative electrode slurry measured by the loading amount measuring unit, The first magnet section and the second magnet section each include a plurality of unit magnets arranged in the width direction of the negative electrode slurry, and the unit magnets individually move up and down in a direction perpendicular to the running electrode sheet, thereby providing a negative electrode magnetic alignment device in which the separation distance between the unit magnets facing each other is adjusted around the electrode sheet.

[0013] In this case, the control unit may include a database in which a reference interval value between the first magnet unit and the second magnet unit according to a loading amount of negative electrode slurry is stored, and may calculate a reference interval value corresponding to the loading amount of negative electrode slurry measured by the loading amount measuring unit, thereby adjusting the separation distance between the first magnet unit and the second magnet unit.

[0014] Here, the distance between the first magnet portion and the second magnet portion may be 10 mm to 50 mm.

[0015] In addition, each unit magnet provided in the first magnet unit and the second magnet unit may include a support part individually fixed to each unit magnet, and a distance adjustment means connected to the support part and inducing the lifting and lowering movement of the support part in a direction perpendicular to the running electrode sheet.

[0016] Additionally, the first and second magnet portions may include magnets having opposite poles.

[0017] The loading amount measuring unit may include at least one of a web gauge and an ultrasonic sensor.

[0018] Here, the ultrasonic sensor may include an ultrasonic generator that scans a surface of the negative electrode slurry with ultrasonic waves, an ultrasonic receiver that receives ultrasonic waves returned after the ultrasonic waves generated by the ultrasonic generator scan the loaded electrode slurry, and a data transmitter that calculates the loading amount of the negative electrode slurry from data obtained by the scan and transmits the calculated amount to a control unit.

[0019] Also, the magnetic alignment device may further include a drying unit that dries the negative electrode slurry in which the carbon-based negative electrode active material is aligned by the first magnet unit and the second magnet unit.

[0020] In one embodiment, the present invention further comprises: applying a negative electrode slurry including a carbon-based negative electrode active material onto a negative electrode current collector; Aligning a carbon-based negative electrode active material contained in a negative electrode slurry using a magnetic alignment device according to the present invention; and drying the negative electrode slurry in which the carbon-based negative electrode active material is aligned to form a negative electrode active layer. The step of aligning the carbon-based negative electrode active material provides a method for manufacturing a negative electrode, in which the distance between the negative electrode slurry and the magnet part of the magnetic alignment device is controlled according to the loading amount of the negative electrode slurry.

[0021] Here, the negative electrode slurry is 100 mg / 25 cm 2 ~500mg / 25cm 2 The coating may be applied at a loading of 0.1g / ml.

[0022] In addition, the negative electrode active layer formed on the negative electrode current collector may have an alignment degree (OI) of the carbon-based negative electrode active material represented by the following formula 1 of 0.1 to 5.0.

[0023] [Formula 1] OI=I 004 / I 110

[0024] In formula 1, I 004 indicates the area of ​​the peak representing the (004) crystal plane in the X-ray diffraction spectroscopy (XRD) measurement of the negative electrode active layer, I 110 indicates the area of ​​the peak indicating the (110) crystal plane when the negative electrode active layer is measured by X-ray diffraction spectroscopy (XRD). Effect of the Invention

[0025] The magnetic alignment device according to the present invention can measure the loading amount of the negative electrode slurry applied onto the negative electrode current collector in real time, and can easily control the strength of the magnetic field by individually adjusting the separation distance between the unit magnets constituting the magnet array of the magnet unit according to the measured loading amount of the negative electrode slurry, thereby providing an advantage that the degree of alignment of the crystal planes of the carbon-based negative electrode active material contained in the manufactured negative electrode active layer is uniformly high. [Brief description of the drawings]

[0026] [Figure 1] 1 is a structural diagram showing a schematic configuration of a magnetic alignment device according to the present invention; [Diagram 2] 13 is an image showing the alignment of the ab-axis crystal planes of graphite depending on whether or not a magnetic field is applied to a negative electrode slurry during the formation of a negative electrode active layer, where (a) shows the case where no magnetic field is applied and the graphite crystal planes are not aligned, and (b) shows the case where a magnetic field is applied and the graphite crystal planes are aligned. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] Since the present invention can be modified in various ways and can have various embodiments, specific embodiments are described in detail in the detailed description.

[0028] However, this is not intended to limit the invention to any particular embodiment, but is understood to include all modifications, equivalents, or alternatives falling within the spirit and scope of the invention.

[0029] In the present invention, the terms "comprise" and "have" are intended to specify the presence of features, numbers, steps, operations, components, parts, or combinations thereof described in the specification, but are understood as not precluding the presence or additional possibility of one or more other features, numbers, steps, operations, components, parts, or combinations thereof.

[0030] In addition, in the present invention, when a layer, film, region, plate, or other portion is described as being "on" another portion, this includes not only the case where it is "directly on" the other portion, but also the case where there is another portion in between. Conversely, when a layer, film, region, plate, or other portion is described as being "under" the other portion, this includes not only the case where it is "directly under" the other portion, but also the case where there is another portion in between. In addition, in the present application, being "on" can include not only the case where it is located at the top, but also the case where it is located at the bottom.

[0031] In the present invention, "containing as a main component" may mean containing 50% by weight or more (or 50% by volume or more), 60% by weight or more (or 60% by volume or more), 70% by weight or more (or 70% by volume or more), 80% by weight or more (or 80% by volume or more), 90% by weight or more (or 90% by volume or more), or 95% by weight or more (or 95% by volume or more) of the defined component relative to the total weight (or total volume). For example, "containing graphite as a main component as a negative electrode active material" may mean containing 50% by weight or more, 60% by weight or more, 70% by weight or more, 80% by weight or more, 90% by weight or more, or 95% by weight or more of graphite relative to the total weight of the negative electrode active material, and in some cases, it may mean that the entire negative electrode active material is made of graphite and contains 100% by weight of graphite.

[0032] In addition, in this specification, "the carbon-based negative electrode active material is oriented" or "the carbon-based negative electrode active material is aligned" may mean that a specific crystal plane (e.g., the ab-axis crystal plane of graphite) showing a two-dimensional planar structure of the carbon-based negative electrode active material constituting the negative electrode active material particles is arranged to have a predetermined inclination based on the surface of the negative electrode current collector, as shown in (b) of Figure 2. This may be different from the case where the particles of the carbon-based negative electrode active material themselves are aligned in a predetermined direction only inside the negative electrode active layer, but have no directionality with respect to the negative electrode current collector, as shown in (a) of Figure 2.

[0033] In addition, "high orientation of the carbon-based negative electrode active material" may mean that a specific crystal plane (e.g., the ab-axis crystal plane of graphite) showing a two-dimensional planar structure of the carbon-based negative electrode active material contained in the negative electrode active layer has a high frequency of having a certain inclination with respect to the surface of the negative electrode current collector. In some cases, it may mean that the crystal plane of the carbon-based negative electrode active material contained in the negative electrode active layer is aligned at a high angle (e.g., an angle close to vertical, more than 45°, specifically 60° or more) with respect to the surface of the negative electrode current collector.

[0034] In addition, "high degree of alignment of carbon-based negative electrode active material" may mean that the "degree of alignment (OI)" referred to in this specification is large, and a specific crystal plane (e.g., the ab-axis crystal plane of graphite) showing a two-dimensional planar structure of the carbon-based negative electrode active material contained in the negative electrode active layer is aligned at a low angle (e.g., less than 45°) with respect to the surface of the negative electrode current collector. Conversely, "low degree of alignment of carbon-based negative electrode active material" may mean that the "degree of alignment (OI)" is small, and the crystal plane of the carbon-based negative electrode active material contained in the negative electrode active layer is aligned at a high angle (e.g., an angle close to vertical, 45° or more, specifically 60° or more) with respect to the surface of the negative electrode current collector.

[0035] Furthermore, in this specification, the term "average particle size (D 50 ) refers to the particle size at which the cumulative value in the particle size distribution of the particles is 50%, and is also called the median diameter.

[0036] The present invention will now be described in more detail.

[0037] <Negative electrode magnetic alignment device> In one embodiment, the present invention comprises: A magnetic alignment device for a negative electrode, which applies a magnetic force to a negative electrode sheet in which a negative electrode slurry containing a carbon-based negative electrode active material is applied onto a negative electrode current collector, thereby orienting the carbon-based negative electrode active material, a first magnet portion and a second magnet portion respectively disposed above and below the traveling electrode sheet; a loading amount measuring unit that is disposed upstream of the first magnet unit and the second magnet unit with respect to the running direction of the electrode sheet and that measures a loading amount of the negative electrode slurry disposed on the electrode sheet; a control unit that adjusts a distance between the first magnet unit and the second magnet unit according to a loading amount of the negative electrode slurry measured by the loading amount measuring unit, The first magnet section and the second magnet section each include a plurality of unit magnets arranged in the width direction of the negative electrode slurry, and the unit magnets individually perform vertical lifting and lowering movements relative to the running electrode sheet, thereby providing a negative electrode magnetic alignment device in which the separation distance between the unit magnets facing each other is adjusted around the electrode sheet.

[0038] The magnetic alignment device for a negative electrode according to the present invention is an apparatus applied in the manufacture of a negative electrode for use in a secondary battery, and can align the carbon-based negative active material contained in the negative electrode slurry in a direction perpendicular to the negative electrode current collector by applying a magnetic field to the surface of the negative electrode current collector coated with a negative electrode slurry containing a carbon-based negative electrode active material, i.e., the surface of the negative electrode slurry. Here, the magnetic alignment device can measure the condition of the negative electrode slurry coated on the negative electrode current collector when the magnetic field is applied, specifically, the loading amount of the negative electrode slurry, in real time, and control the strength of the magnetic field of the magnet unit disposed above and below the electrode sheet during the movement. As a result, the magnetic alignment device can realize uniform alignment of the carbon-based negative electrode active material contained in the negative electrode slurry, and the negative electrode manufactured in this way can exhibit the effect of increasing the mobility of lithium ions during charging and discharging of the battery, reducing resistance, and improving charge and discharge performance.

[0039] Here, being aligned in a direction perpendicular to the negative electrode current collector means that the crystal plane of the carbon-based negative electrode active material is aligned. Specifically, "the carbon-based negative electrode active material is aligned perpendicular to the negative electrode current collector" may mean that the crystal plane of the carbon-based negative electrode active material constituting the spherical particles, specifically, the crystal plane showing the plane direction of the graphite having a two-dimensional structure among the crystal planes of graphite, is aligned perpendicular to the surface of the negative electrode current collector. At this time, the plane direction of the graphite may have an average inclination of 60 to 120° with respect to the negative electrode current collector, and preferably has an average inclination of 70 to 110° or 80 to 100°.

[0040] For this purpose, the magnetic alignment device 10 according to the present invention includes a first magnet unit 120a and a second magnet unit 120b, which are respectively disposed above and below a traveling electrode sheet, i.e., a negative electrode current collector C on which a negative electrode slurry S is applied, as shown in FIG. 1, a loading amount measuring unit 110, which is disposed upstream of the first magnet unit 120a and / or the second magnet unit 120b based on the traveling direction of the electrode sheet and measures the loading amount of the negative electrode slurry S on the electrode sheet, and a control unit 130, which adjusts the distance between the first magnet unit 120a and the second magnet unit 120b according to the loading amount of the negative electrode slurry measured by the loading amount measuring unit.

[0041] In the magnetic alignment device 10, the loading amount measuring unit 110 is located upstream of the first magnet unit 120a and / or the second magnet unit 120b based on the running direction of the electrode sheet, and serves to measure the loading amount of the negative electrode slurry S before the magnetic field applied by the magnet unit affects the negative electrode slurry. In this case, the loading amount measuring unit 110 may be applied without any particular limitation as long as it is a means / method commonly used in the art for measuring the loading amount of the negative electrode slurry S, and may include a non-contact measuring device that can prevent loss and / or change in state of the negative electrode slurry. As an example, the loading amount measuring unit 110 may include one or more of a web gauge and an ultrasonic sensor. Here, the ultrasonic sensor may include an ultrasonic receiving unit that receives the returned ultrasonic wave after scanning the loaded negative electrode slurry with the generated ultrasonic wave, and a data transmitting unit that calculates the loading amount of the negative electrode slurry from data obtained by the scan and transmits the calculated amount to the control unit.

[0042] In addition, in order to measure the loading amount of the negative electrode slurry S more precisely, the loading amount measuring unit 110 may measure the loading amount of the negative electrode slurry S in real time by arranging two or more non-contact measuring devices in the width direction of the running negative electrode slurry S. The measured loading amount values ​​are transmitted to the control unit, and an average value thereof may be reflected as the loading amount of the negative electrode slurry. In this case, there is an advantage that the loading amount of the negative electrode slurry applied using a die coater or the like may be measured more precisely.

[0043] In addition, the loading amount measuring unit 110 may include two or more non-contact measuring devices along the running direction of the electrode sheet. Specifically, the loading amount measuring unit 110 may include a first measuring device 111 and a second measuring device 112 that are continuously arranged along the running direction of the electrode sheet. In this case, it is possible to reduce an error rate for the loading amount of the negative electrode slurry measured in real time.

[0044] In the magnetic alignment device 10, the control unit 130 may play a role in controlling the separation distance between the first magnet unit 120a and the second magnet unit 120b. To this end, the magnetic alignment device 10 may receive the loading amount of the negative electrode slurry S measured by the loading amount measurement unit 110, compare the loading amount of the negative electrode slurry S with a reference interval value to recognize a reference interval value corresponding to the measured loading amount of the negative electrode slurry, and transmit the recognized reference interval value to the first magnet unit 120a and the second magnet unit 120b, respectively, to adjust the separation distance between the first magnet unit 120a and the second magnet unit 120b.

[0045] Here, the reference interval value refers to a value indicating the interval, i.e., the separation distance, between the first magnet unit 120a and the second magnet unit 120b according to the loading amount of the negative electrode slurry S. This value may be stored in a database (not shown) included in the control unit 130. The reference interval value may be a value obtained by obtaining data regarding the separation distance between the first magnet unit 120a and the second magnet unit 120b according to the loading amount of the negative electrode slurry S using an existing conventional measuring device, selecting only data that most effectively embodies the alignment of the carbon-based negative electrode active material contained in the negative electrode slurry from the obtained data, and storing the selected value in the database.

[0046] In addition, even if the loading amount of the negative electrode slurry S is the same, the content of the carbon-based negative electrode active material may differ depending on the density (or concentration) of the carbon-based negative electrode active material contained in the negative electrode slurry. In addition, since the content of the carbon-based negative electrode active material affects the alignment of the crystal plane with respect to the negative electrode current collector C, the strength of the magnetic field may be adjusted according to the content during alignment. Therefore, the database may further include density (or concentration) information on the carbon-based negative electrode active material in the negative electrode slurry for each loading amount of the negative electrode slurry S to correct the loading amount of the negative electrode slurry S, along with information on the separation distance between the first magnet unit 120a and the second magnet unit 120b according to the loading amount of the negative electrode slurry S.

[0047] In addition, since the density (or concentration) of the carbon-based negative electrode active material may affect the magnetic field strength due to the compensation for the loading amount of the negative electrode slurry S as described above, the interval reference value stored in the database may be a value reflecting data on the density (or concentration) of the carbon-based negative electrode active material in the negative electrode slurry stored in the database.

[0048] Furthermore, in the magnetic alignment device 10, the first magnet section 120a and the second magnet section 120b are disposed above and below the traveling electrode sheet, respectively, and serve to apply a magnetic field to the surface of the negative electrode slurry S.

[0049] Here, the first magnet unit 120a and the second magnet unit 120b may each include a plurality of unit magnets along the width direction of the negative electrode slurry S in order to apply a magnetic field to the surface of the negative electrode slurry S. Also, the plurality of unit magnets may each include a means for adjusting the interval between them, i.e., the separation distance, by performing a lifting and lowering movement at the top and bottom of the negative electrode slurry. For this purpose, the first magnet unit 120a and the second magnet unit 120b may each include a first magnet row 122a and a second magnet row 122b in which a plurality of unit magnets are arranged along the width direction of the running negative electrode slurry, a support unit (not shown) that is individually fixed to each unit magnet provided in the magnet rows 122a and 122b, and distance adjustment units 121a and 121b that are connected to the support unit and induce the lifting and lowering movement of the support unit (or the lifting and lowering movement of the unit magnets) in a direction perpendicular to the running electrode sheet.

[0050] At this time, the distance adjusting means 121a and 121b may operate to receive a reference interval value from the control unit 130 and adjust the separation distance between the first magnet unit 120a and the second magnet unit 120b according to the received reference interval value.

[0051] The first magnet unit 120a and the second magnet unit 120b have such a configuration, and thus the strength of the magnetic field applied to the negative electrode slurry S can be easily controlled by adjusting the distance between them. That is, the strength of the magnetic field applied to the negative electrode slurry S can be increased as the distance between the first magnet unit 120a and the second magnet unit 120b becomes narrower, and the strength of the magnetic field applied to the negative electrode slurry S can be decreased as the distance between them becomes wider.

[0052] In addition, the first magnet unit 120a and the second magnet unit 120b may be positioned in the width direction of the negative electrode slurry S to face each other and be arranged to have opposite poles. For example, the N pole of the first magnet row 122a of the first magnet unit 120a may face the S pole of the second magnet row 122b of the second magnet unit 120b, or the S pole of the first magnet row 122a of the first magnet unit 120a may face the N pole of the second magnet row 122b of the second magnet unit 120b. When the electrode sheet passes through the space in which the N pole and the S pole face each other in this manner, the vertical alignment of the carbon-based negative electrode active material with respect to the negative electrode current collector C may be more effectively performed between the first magnet unit 120a and the second magnet unit 120b.

[0053] In addition, the first magnet unit 120a is disposed on the upper part of the traveling electrode sheet, and a Halbach array may be applied to the first magnet row 122a in order to apply a strong magnetic field to the carbon-based negative electrode active material of the negative electrode slurry S. Here, the Halbach array is a permanent magnet arrangement, and a magnet with a high magnetic field strength may be provided by gradually changing the magnetization direction of the magnet. When a magnet having a Halbach array is applied as the first magnet row 122a of the first magnet unit 120a, there is an advantage that the strength of the magnetic field applied to the negative electrode slurry S may be adjusted without significantly changing the separation distance between the first magnet unit 120a and the second magnet unit 120b.

[0054] Meanwhile, the distance between the first magnet portion 120a and the second magnet portion 120b may be 10 mm to 50 mm, specifically, 10 mm to 40 mm, 20 mm to 50 mm, or 15 mm to 45 mm. Here, the distance between the first magnet portion 120a and the second magnet portion 120b may be the same as the distance between the first magnet array 122a and the second magnet array 122b. In the present invention, the distance between the first magnet portion 120a and the second magnet portion 120b is adjusted to the above range, thereby more efficiently aligning the carbon-based negative electrode active material contained in the negative electrode slurry S.

[0055] In addition, the magnetic alignment device 10 may further include a drying unit 140 for drying the negative electrode slurry S in which the carbon-based negative electrode active material is aligned by the first magnet unit 120a and the second magnet unit 120b.

[0056] The drying section 140 includes a wall (not shown) that blocks the periphery except for an entrance / exit through which the electrode sheet coated with the slurry S is introduced and conveyed out, and a dryer (not shown) for drying the electrode sheet on the wall on the side from which the electrode sheet coated with the electrode slurry is drawn out.

[0057] When the electrode sheet coated with the electrode slurry enters through the inlet of the drying unit 140, energy such as light, heat, and the like supplied from the wall on the opposite side is transferred to the electrode sheet. Therefore, the wall is preferably made of a heat insulating material to prevent internal energy from being transferred to the outside and causing heat loss.

[0058] In addition, the dryer may have a configuration that performs a two-stage drying process to maintain the alignment of the carbon-based negative electrode active material contained in the negative electrode active layer, although the type of the dryer is not limited thereto. Specifically, the dryer may include a first dryer that dries the negative electrode slurry using light and a second dryer that dries the negative electrode slurry using heat, and the first dryer and the second dryer may be operated continuously to dry the negative electrode slurry.

[0059] The first dryer is a device for pre-drying the negative electrode slurry, and may irradiate light or wavelengths onto the surface of the negative electrode slurry as described above. In general, the negative electrode slurry may be dried by applying hot air at a high temperature. However, in this case, the drying time of the negative electrode slurry becomes long, and the alignment of the carbon-based negative electrode active material in the negative electrode slurry may be disturbed. In addition, if the temperature of the hot air is increased to solve this problem, the tendency of drying at the surface of the slurry increases, and a phenomenon (migration) in which the binder is concentrated on the surface of the slurry due to the volatilized solvent occurs, resulting in a decrease in the adhesive strength between the active material layer and the negative electrode current collector. In order to dry the negative electrode slurry while maintaining a high degree of alignment of the carbon-based negative electrode active material without such problems, the present invention may be configured to pre-dry the electrode slurry by irradiating energy in the form of light or wavelengths using the first dryer. The first dryer may include, for example, an ultraviolet dryer, a near infrared dryer, a far infrared dryer, etc., and may specifically include a far infrared dryer that emits energy with a wavelength of 1 μm or more, more specifically, 5 μm or more, 10 μm or more, or 20 μm or more in order to realize a uniform drying speed of the electrode slurry. The far infrared dryer has a long light or wavelength and is highly energy efficient, unlike near infrared dryers and infrared rays commonly used in the industry. Furthermore, the far infrared dryer has the advantage that it can apply energy uniformly not only to the surface of the negative electrode slurry but also to the inside, thereby increasing the adhesive strength between the negative electrode slurry and the negative electrode current collector in a short time.

[0060] At this time, the first dryer is 50 kW / m 2 ~1,000kW / m 2 It can emit energy at a power density of 50 kW / m 2 ~500kW / m 2 , 50kW / m 2 ~250kW / m 2 , or 50 kW / m 2 , and 200 kW / m 2In the present invention, by controlling the power density of the first dryer within the above range, it is possible to prevent uneven drying of the active material layer caused by an excessive power density.

[0061] In addition, the second dryer may apply heat to the negative electrode slurry pre-dried by light or wavelength to uniformly and completely dry it. The second dryer may include any dryer commonly used in the art without any particular limitation, and may include, for example, a hot air dryer, a vacuum oven, etc., used alone or in combination.

[0062] Since the magnetic alignment device according to the present invention has the above-mentioned configuration, it can reflect the state of the negative electrode slurry in real time and uniformly induce the alignment of the internal carbon-based negative electrode active material. Therefore, the manufactured negative electrode can exhibit the effect of increasing the mobility of lithium ions and reducing the resistance during charging and discharging of the battery, thereby improving the charge and discharge performance.

[0063] <Method of manufacturing the negative electrode> In one embodiment, the present invention further comprises: applying a negative electrode slurry including a carbon-based negative electrode active material onto a negative electrode current collector; Aligning the carbon-based negative electrode active material contained in the negative electrode slurry using the magnetic alignment device according to the present invention; and drying the negative electrode slurry in which the carbon-based negative electrode active material is aligned to form a negative electrode active layer. The step of aligning the carbon-based negative electrode active material provides a method for manufacturing a negative electrode, in which the distance between the negative electrode slurry and the magnet part of the magnetic alignment device is controlled according to the loading amount of the negative electrode slurry.

[0064] The method for manufacturing a negative electrode according to the present invention can align the carbon-based negative active material in the negative electrode slurry to be perpendicular to the surface of the negative electrode current collector (or to the running direction of the electrode sheet) by applying a magnetic field to the surface of the applied negative electrode slurry using the magnetic alignment device of the present invention described above. In addition, the manufacturing method can form a negative electrode active layer in which the vertical alignment of the carbon-based negative active material is maintained by subsequently continuously drying the negative electrode slurry.

[0065] The method for manufacturing the negative electrode can reflect the state of the negative electrode slurry, specifically, the loading amount, in real time by using the magnetic alignment device described above, and can uniformly induce alignment of the internal carbon-based negative electrode active material. Therefore, the manufactured negative electrode can exhibit an effect of increasing the mobility of lithium ions and reducing resistance during charging and discharging of the battery, thereby improving charge and discharge performance.

[0066] Here, the steps of applying the negative electrode slurry to the negative electrode current collector and drying the negative electrode slurry may be performed in a manner commonly used in the art.

[0067] In addition, the negative electrode slurry may be applied to have a loading amount within a certain range in consideration of the alignment efficiency of the carbon-based negative electrode active material included in the negative electrode slurry and the drying efficiency of the negative electrode slurry.

[0068] As an example, the negative electrode slurry is 100 mg / 25 cm 2 ~500mg / 25cm 2 Specifically, the coating may be applied at a loading of 150 mg / 25 cm 2 ~450mg / 25cm 2 , 150mg / 25cm 2 ~200mg / 25cm 2 , 200mg / 25cm 2 ~400mg / 25cm 2 , 200mg / 25cm 2 ~300mg / 25cm 2 , 250mg / 25cm 2~400mg / 25cm 2 , or 180 mg / 25 cm 2 ~420mg / 25cm 2 The coating may be applied at a loading of 0.1g / ml.

[0069] In addition, in the step of aligning the carbon-based negative active material contained in the negative electrode slurry using a magnetic alignment device, the magnetic field application conditions may be controlled to improve the alignment efficiency of the carbon-based negative active material. Specifically, the degree of alignment of the carbon-based negative active material may be controlled by the strength, application time, etc. of the magnetic field.

[0070] For example, the magnetic field may be applied at a magnetic field strength of 0.5 to 2.0T, and more specifically, at a magnetic field strength of 0.9 to 1.5T, 1.0 to 1.4T, or 1.0 to 1.2T.

[0071] Moreover, the magnetic field may be applied for 0.1 to 20 seconds, and more specifically, for 0.5 to 15 seconds, 0.5 to 12 seconds, 1 to 10 seconds, or 2 to 8 seconds.

[0072] <Negative electrodes for lithium secondary batteries> In one embodiment, the present invention provides a negative electrode manufactured using the magnetic alignment apparatus according to the present invention described above.

[0073] The negative electrode prepared according to the present invention includes a carbon-based negative electrode active material and a negative electrode active layer on at least one surface of a negative electrode current collector, and the negative electrode active layer may have an alignment degree (OI) of the carbon-based negative electrode active material represented by the following Formula 1 of 0.1 to 5.0.

[0074] [Formula 1] OI=I 004 / I 110

[0075] In formula 1, I 004 indicates the area of ​​the peak representing the (004) crystal plane in the X-ray diffraction spectroscopy (XRD) measurement of the negative electrode active layer, I 110indicates the area of ​​the peak indicating the (110) crystal plane when the negative electrode active layer is measured by X-ray diffraction spectroscopy (XRD).

[0076] The negative electrode for a lithium secondary battery according to the present invention includes a negative electrode active layer including a carbon-based negative electrode active material on both sides of a negative electrode current collector. The negative electrode active layer is a layer that realizes the electrical activity of the negative electrode, and is manufactured by applying an electrode slurry including a negative electrode active material that realizes an electrochemical oxidation-reduction reaction during charging and discharging of the battery to both sides of the electrode current collector, and then drying and rolling the same. The negative electrode active layer includes a carbon-based negative electrode active material as a negative electrode active material to realize electrical activity through a reversible oxidation-reduction reaction during charging and discharging of the battery. Specifically, the carbon-based negative electrode active material means a material mainly composed of carbon atoms, and such a carbon-based negative electrode active material may include graphite. The graphite may include at least one of natural graphite and artificial graphite, and preferably includes natural graphite or a mixture of natural graphite and artificial graphite. For example, the carbon-based negative electrode active material may contain natural graphite or artificial graphite alone, or may contain a mixture of natural graphite and artificial graphite in some cases. In this case, the mixture ratio of natural graphite to artificial graphite may be 5-40:60-95, or 10-30:70-90, based on weight. By containing natural graphite and artificial graphite in the above-mentioned mixture ratio, the carbon-based negative electrode active material may realize high orientation of the carbon-based negative electrode active material on the surface of the negative electrode current collector while strengthening the adhesion between the negative electrode current collector and the negative electrode active layer.

[0077] The carbon-based negative electrode active material is preferably a spherical graphite granule formed by the aggregation of a plurality of flake graphite. Examples of flake graphite include natural graphite, artificial graphite, mesophase calcined carbon (bulk mesophase) made from tar and pitch, graphitized cokes (raw coke, green coke, pitch coke, needle coke, petroleum coke, etc.), etc. In particular, a graphite granule assembled from a plurality of highly crystalline natural graphites is preferable. In addition, one graphite granule may be formed by the aggregation of 2 to 100 flake graphite particles, preferably 3 to 20 flake graphite particles.

[0078] Such a carbon-based negative electrode active material, specifically, graphite, may have a spherical particle shape, and the sphericity of the graphite particles may be 0.75 or more, for example, 0.75 to 1.0, 0.75 to 0.95, 0.8 to 0.95, or 0.90 to 0.99. Here, the "sphericity" may mean the ratio of the shortest diameter (minor axis) to the longest diameter (major axis) among any diameters passing through the center of the particle, and when the sphericity is 1, it means that the particle shape is spherical. The sphericity may be measured using a particle shape analyzer. The present invention has the advantages of realizing a shape of the carbon-based negative electrode active material close to a sphere, thereby realizing high electrical conductivity of the negative electrode active layer, thereby improving the capacity of the battery, and increasing the specific surface area of ​​the negative electrode active material, thereby improving the adhesive force between the negative electrode active layer and the current collector.

[0079] In addition, the carbon-based negative electrode active material has an average particle size (D 50 ), specifically, the average particle size (D 50 ) can be shown.

[0080] The average particle size of spherical natural graphite is preferably as small as possible to maximize the degree of disorder in the direction of expansion of each particle so as to prevent the expansion of the particles due to charging of lithium ions. However, when the particle size of natural graphite is less than 0.5 μm, a large amount of binder is required due to the increase in the number of particles per unit volume, and the sphericity and sphericity yield may be reduced. On the other hand, when the maximum particle size exceeds 10 μm, the expansion becomes intense, and the adhesion between particles and between the particles and the current collector decreases due to repeated charging and discharging, and the cycle characteristics may be significantly reduced.

[0081] In the negative electrode active layer including such a carbon-based negative electrode active material, the degree of alignment of the carbon-based negative electrode active material can be controlled to a constant level. The present invention can reduce electrode resistance by aligning the crystal plane of the carbon-based negative electrode active material contained in the negative electrode active layer in a constant direction, thereby improving the charging performance of the negative electrode active layer.

[0082] Here, the degree of alignment (i.e., orientation) of the carbon-based negative electrode active material (e.g., graphite) can be determined by crystal plane analysis of graphite.

[0083] As an example, in the negative electrode active layer, the carbon-based negative electrode active material is aligned perpendicularly to the negative electrode current collector, and the degree of alignment (OI) of the carbon-based negative electrode active material, represented by the following Equation 1, may satisfy 0.1 to 5.0 when the negative electrode active layer is measured by X-ray diffraction spectroscopy (XRD).

[0084] [Formula 1] OI=I 004 / I 110

[0085] In formula 1, I 004 indicates the area of ​​the peak representing the (004) crystal plane in the X-ray diffraction spectroscopy (XRD) measurement of the negative electrode active layer, I 110 indicates the area of ​​the peak indicating the (110) crystal plane when the negative electrode active layer is measured by X-ray diffraction spectroscopy (XRD).

[0086] The crystal plane orientation of the carbon-based negative electrode active material can be determined by a crystal plane analysis of the carbon-based negative electrode active material, such as X-ray diffraction spectroscopy. The degree of alignment (OI) of the carbon-based negative electrode active material represented by the above formula 1 can be an index indicating the direction in which the crystal structure of the carbon-based negative electrode active material is aligned during X-ray diffraction measurement, specifically, the degree to which the ab-axis crystal plane indicating the two-dimensional planar structure of the carbon-based negative electrode active material is aligned with respect to the surface of the negative electrode current collector. For example, when the negative electrode active layer contains graphite as the carbon-based negative electrode active material, the negative electrode active layer exhibits 2θ=26.5±0.2°, 42.4±0.2°, 43.4±0.2°, 44.6±0.2°, 54.7±0.2°, and 77.5±0.2°, which are peaks for graphite during X-ray diffraction spectroscopy analysis. This refers to the (002) plane, (100) plane, (101)R plane, (101)H plane, (004) plane, and (110) plane of the crystal planes of graphite contained in the negative electrode active layer. In general, in the case of graphite, graphene layers are placed on the a-axis and b-axis planes, and such graphene layers are stacked along the c-axis to have a hexagonal or rhombohedral crystal structure. Here, the above crystal plane peak is a peak that indicates the plane characteristics of such a crystal structure. In addition, the peak that appears at 2θ=43.4±0.2° may be considered to be an overlap of the peaks corresponding to the (101)R plane of the carbon-based material and the (111) plane of the current collector, for example, Cu.

[0087] In the present invention, the degree of alignment (OI) of graphite can be measured by the area ratio of the peak at 2θ=77.5±0.2° representing the (110) plane and the peak at 2θ=54.7±0.2° representing the (004) plane, specifically, the area ratio obtained by integrating the intensities of the above peaks. In addition, the X-ray diffraction was measured using CuKα radiation as a target line, and the target line was extracted and measured using a monochromator device to improve the peak intensity resolution. At this time, the measurement conditions were 2θ=10°-90°, a scan speed (° / s) of 0.044-0.089, and a step size of 0.026° / step. In addition, the (004) plane appearing at 2θ=54.7±0.2° indicates the thickness direction characteristic (c-axis direction characteristic) of the layered structure in which the two-dimensional planar structure of the graphite layers is laminated, and the (110) plane appearing at 2θ=77.5±0.2° indicates the planar characteristic (ab-axis direction characteristic) of the laminated graphite layers. Therefore, the smaller the (004) plane peak indicating the thickness direction characteristic of the graphite layer plane, and the larger the (110) plane peak indicating the planar characteristic of the graphite layer, the higher the angle at which the graphite plane is aligned with respect to the negative electrode current collector surface. In other words, the closer the OI value is to 0, the closer the angle or inclination of the graphite layer surface to the negative electrode current collector surface is to 90°, and the larger the OI value is, the closer the inclination to the negative electrode current collector surface is to 0° or 180°. In this aspect, in the negative electrode active layer according to the present invention, since the carbon-based negative electrode active material is aligned perpendicular to the negative electrode current collector, the degree of graphite alignment (OI) may be lower than when a magnetic field is not applied.Specifically, the degree of alignment of the carbon-based negative electrode active material contained in the negative electrode active layer may be 0.1 to 5.0, more specifically, 0.1 to 4.5, 0.1 to 4.0, 0.1 to 3.5, 0.1 to 3.0, 0.1 to 2.5, 0.1 to 2.0, 0.1 to 1.0, 0.5 to 2.9, 1.0 to 4.5, 1.1 to 4.1, 1.5 to 4.0, 1.1 to 3.5, 1.0 to 4 ... It can be 0.5 to 3.0, 0.9 to 2.9, 0.1 to 2.4, 0.1 to 2.1, 0.1 to 1.9, 2.0 to 5.0, 2.0 to 4.0, 2.1 to 3.9, 2.5 to 3.9, 3.1 to 4.5, 0.1 to 0.6, 0.15 to 0.6, 0.15 to 0.5, 0.2 to 0.5, 0.2 to 0.4, 0.25 to 0.45, or 0.3 to 0.5.

[0088] As another example, the negative electrode active layer may have a small degree of alignment of 1.0 or less according to the following Equation 2 when measured by a near edge X-ray fluorescence spectrometer (NEXAFS).

[0089] [Formula 2] S 60 / 0 =I60 B / A / I0 B / A

[0090] In the above formula 2, S 60 / 0 is the peak intensity ratio (I60) at an incident angle of 0° in the near-edge X-ray fluorescence spectrometer (NEXAFS) measurement. B / A ) at an incident angle of 60° (I0 B / A ) value.

[0091] Near-edge X-ray absorption spectra, also known as near-edge NEXAFS (Near Edge X-ray Absorbance Fine Structure) spectra, are absorption spectra observed when electrons (K-shell inner-shell electrons) present in the occupied inner-shell level (1s orbital) of a carbon atom absorb the energy of irradiated X-rays and are excited to various vacant levels that are unoccupied.

[0092] Here, the vacant levels to which the electrons in the core level are excited are the sp2 π assigned to antibonding orbitals of bonds * sp reflecting the level and crystal disorder (edge ​​surface, non-orientation, etc.) 3 σ assigned to antibonding orbitals of bonds * There are vacant levels that belong to the orbitals of the sp bond, or the antibonding orbitals of the CH bond and the CO bond. 2 In graphite, which has a crystal structure in which hexagonal mesh structures formed by bonds are stacked, the flat surfaces of the hexagonal mesh (AB planes described below) are the basal planes, and the surfaces where the edges of the hexagonal mesh appear are the edge planes. On edge planes, carbon may have -C=O at the ends, so sp 3 The binding percentage can be high.

[0093] In addition, unlike X-ray photoelectron spectroscopy (XPS), which measures the bond energy between atoms constituting a compound, the near-edge NEXAFS spectrum reflects the local structure near the carbon atom including the excited core electrons and can also reflect only the surface structure of the measured graphite particle. Therefore, the present invention can measure the crystalline state (orientation) of the carbon-based negative electrode active material, which is a spherical particle, i.e., graphite, by using the near-edge NEXAFS spectrum.

[0094] Meanwhile, the near-edge NEXAFS spectrum can be measured by a total electron count method in which a sample is irradiated with synchrotron radiation having a fixed incident angle with respect to the sample, and the energy of the irradiated synchrotron radiation is scanned from 280 eV to 320 eV to measure a sample current flowing into the sample to supplement photoelectrons emitted from the sample. Specifically, in order to more quantitatively measure the degree of alignment of the carbon-based negative electrode active material contained in the negative electrode active layer, the present invention uses the degree of alignment (S 60 / 0 ) can be measured.

[0095] Generally, synchrotron radiation has a high linear polarization, so the incident direction of the synchrotron radiation is the sp 2 When the bond (-C=C-) is parallel to the bond axis direction, the C1s level is *The absorption peak intensity attributable to the transition to the level becomes large, and conversely, when it is perpendicular, the absorption peak intensity becomes small. Therefore, highly oriented graphite (e.g., HOPG, single crystal graphite) has sp 2 Since the graphite crystals that form the bonds are highly aligned, the spectrum shape changes significantly when the incident angle of the synchrotron radiation on the sample is changed. In contrast, low-oriented graphite (e.g., non-graphitic carbon evaporated film) has sp 2 Because the carbon material that forms bonds has a low degree of orientation, the spectral shape changes very little even when the angle of incidence of the synchrotron radiation on the sample is changed.

[0096] In addition, the negative electrode active layer has a first absorption peak intensity (I A ) to any second absorption peak intensity (I B ) percentage (I B / A ) may vary depending on the incident angle, which may mean that the carbon-based negative electrode active material contained in the measured negative electrode active layer is regularly arranged (i.e., highly oriented). On the other hand, if the proportion I does not vary depending on the incident angle, it may mean that the carbon-based negative electrode active material contained in the measured negative electrode active layer is irregularly arranged (i.e., poorly oriented).

[0097] In the present invention, in order to measure the degree of alignment of the carbon-based negative electrode active material contained in the negative electrode active layer, a near-edge NEXAFS spectrum (i.e., near-edge X-ray fluorescence spectrometer (NEXAFS)) is measured, and synchrotron radiation is incident on the negative electrode active layer at different incident angles (0° and 60°) to obtain a C1s level to π * The intensity of the absorption peak (peak A = 287 ± 0.2 eV) attributable to the transition to the C1s level versus σ * The ratio of the intensity of the absorption peak (peak B = 293 ± 0.2 eV) attributable to the transition to the level (I B / A ), the ratio of the intensity ratio between the incidence angles (60° and 0°) (S 60 / 0 =I60 B / A / I0 B / A) the degree of alignment of the carbon-based negative electrode active material can be quantitatively measured.

[0098] That is, the degree of alignment of the carbon-based negative electrode active material contained in the negative electrode active layer is expressed by i) the C1s level measured at an incident angle of 60° to π * Absorption peak intensity (peak A = 287 ± 0.2 eV) attributed to the transition to the level (I60 A ) for the absorption peak (peak B = 293 ± 0.2 eV) intensity attributable to the transition from the C1s level to the σ level (I60 B ) percentage (I60 B / A ) is calculated, and ii) π * The intensity of the absorption peak (peak A = 287 ± 0.2 eV) attributed to the transition to the level (I0 A ) from the C1s level to σ * Absorption peak intensity (peak B = 293 ± 0.2 eV) attributable to the transition to the level (I0 B ) percentage (I0 B / A ) and then iii) calculate the ratio of these (S 60 / 0 =I60 B / A / I0 B / A ) can be evaluated.

[0099] [Formula 3] I60 B / A =I60 B / I60 A

[0100] [Formula 4] I0 B / A =I0 B / I0 A

[0101] In Equation 3 and Equation 4, I60 A indicates the intensity of the strongest peak among the peaks present at 286±1.0 eV when the incident angle is 60°, I60 Bindicates the intensity of the strongest peak among the peaks present at 292.5±1.0 eV when the incident angle is 60°, I0 A indicates the intensity of the strongest peak among the peaks present at 286±1.0 eV when the incident angle is 0°, I0 B indicates the intensity of the strongest peak among the peaks present at 292.5±1.0 eV when the incident angle is 0°.

[0102] Here, the above S 60 / 0 The closer to 1, the lower the degree of alignment of the graphite crystals, and the closer to 0, the higher the degree of alignment of the graphite crystals. 60 / 0 ) may be 1.0 or less, and more specifically may be 0.9 or less, 0.8 or less, 0.7 or less, 0.1 to 0.7, or 0.3 to 0.7.

[0103] Furthermore, in the negative electrode active layer, vertical alignment of the carbon-based negative electrode active material with respect to the negative electrode current collector may be uniformly induced, and the alignment deviation of a plurality of carbon-based negative electrode active materials measured arbitrarily per unit area may be low.

[0104] For example, in the negative electrode active layer, when X-ray diffraction spectroscopy (XRD) is measured at any three points in a unit area (10 cm x 10 cm) of the negative electrode active layer, the alignment deviation of the carbon-based negative electrode active material represented by Formula 1 may be less than 5% based on the average value, specifically, 4% or less, 3% or less, 2% or less, or 1% or less.

[0105] In another example, the negative electrode active layer may have an alignment deviation of the carbon-based negative electrode active material represented by Equation 2 of less than 5% based on the average value when measured by a near-edge X-ray fluorescence spectrometer (NEXAFS) at any three points present in a unit area (10 cm x 10 cm) of the negative electrode active layer, specifically, 4% or less, 3% or less, 2% or less, or 1% or less.

[0106] Meanwhile, the negative electrode active layer according to the present invention may further selectively contain a conductive material, a binder, other additives, and the like, in addition to the negative electrode active material, as necessary.

[0107] The conductive material may include, but is not limited to, one or more of carbon black, acetylene black, ketjen black, carbon nanotubes, carbon fibers, and the like.

[0108] As an example, the negative electrode active layer may contain carbon nanotubes or carbon fibers as conductive materials, either alone or in combination.

[0109] At this time, the content of the conductive material may be 0.1 to 10 parts by weight, specifically 0.1 to 8 parts by weight, 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, or 2 to 6 parts by weight, based on 100 parts by weight of the total negative electrode active layer. By controlling the content of the conductive material within the above range, the present invention can prevent a decrease in charge capacity due to an increase in the resistance of the negative electrode caused by a low content of the conductive material. In addition, by controlling the content of the conductive material within the above range, the present invention can prevent problems such as a decrease in the content of the negative electrode active material due to an excessive amount of the conductive material, resulting in a decrease in charge capacity, or a decrease in rapid charge characteristics due to an increase in the loading amount of the negative electrode active layer.

[0110] In addition, the binder is a component that aids in bonding between the active material and the conductive material and the current collector, and may be suitably applied within a range that does not deteriorate the electrical properties of the electrode. Specifically, the binder may include any one or more selected from vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, and fluororubber.

[0111] The content of the binder may be 0.1 to 10 parts by weight, specifically 0.1 to 8 parts by weight, 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, or 2 to 6 parts by weight, based on 100 parts by weight of the total negative electrode active layer. By controlling the content of the binder contained in the negative electrode active layer within the above range, the present invention can prevent a decrease in adhesive strength of the active layer due to a low content of the binder, or a decrease in electrical properties of the electrode due to an excessive amount of the binder.

[0112] The negative electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and may be, for example, copper, stainless steel, nickel, titanium, calcined carbon, etc., and in the case of copper or stainless steel, it may be surface-treated with carbon, nickel, titanium, silver, etc. The average thickness of the negative electrode current collector may be suitably 1 to 500 μm, taking into consideration the conductivity and total thickness of the negative electrode to be manufactured.

[0113] The present invention will now be described in more detail with reference to examples and experimental examples.

[0114] However, the following examples and experimental examples are merely illustrative of the present invention, and the content of the present invention is not limited to the following examples and experimental examples.

[0115] <Examples 1 and 2. Production of negative electrodes for lithium secondary batteries> A negative electrode was manufactured using the magnetic alignment apparatus of the present invention having the structure shown in FIG. 1, and the number of non-contact measuring devices installed in the loading amount measuring unit was adjusted as shown in Table 1 to manufacture a negative electrode for a lithium secondary battery.

[0116] Specifically, natural graphite was first prepared as the negative electrode active material, and 97 parts by weight of the negative electrode active material and 3 parts by weight of styrene butadiene rubber (SBR) were mixed with water to form a negative electrode slurry. The negative electrode slurry was then cast using a die coater onto a thin copper plate that was being transported roll-to-roll (transport speed: 3 m / min).

[0117] At this time, the average loading amount of the applied negative electrode slurry was 200 mg / 25 cm 2 The negative electrode slurry was cast onto the copper sheet for 20 seconds so that the average loading amount of the continuously applied negative electrode slurry was 400 mg / 25 cm 2 The negative electrode slurry was cast onto a copper sheet for 20 seconds so that the negative electrode slurry was

[0118] Thereafter, a magnetic field was applied to the negative electrode slurry by moving the copper sheet so that the applied negative electrode slurry passed through the loading amount measurement section and between the first magnet section and the second magnet section.

[0119] At this time, the loading amount measuring unit included a web gauge as a non-contact measuring device, and the confocal measuring devices were included in the number shown in Table 1 below along the running direction of the copper sheet. In addition, the negative electrode slurry loading amount measured by the loading amount measuring unit was transmitted to a control unit, and the control unit recognized a gap reference value corresponding to the measured negative electrode slurry loading amount by comparing it with a gap reference value stored in a database, and transmitted the recognized gap reference value to the first magnet unit and the second magnet unit, respectively.

[0120] In addition, the first magnet unit and the second magnet unit individually adjusted the separation distance between the unit magnets in the first magnet row (including 5 to 20 unit magnets) and the second magnet row (including 5 to 20 unit magnets) fixed to the support unit by adjusting the distance adjustment means in accordance with the reference interval value transmitted from the control unit. Here, the separation distance between the first magnet row and the second magnet row was adjusted to 20 to 40 mm in accordance with the reference interval value transmitted from the control unit, and the strength of the applied magnetic field was 1.0 T.

[0121] [Table 1]

[0122] The copper thin plate to which the magnetic field was applied was moved to a drying section to dry the negative electrode slurry, thereby producing a negative electrode for a lithium secondary battery.

[0123] <Comparative Example 1. Production of negative electrode for lithium secondary battery> A negative electrode for a lithium secondary battery was manufactured in the same manner as in Example 1, except that a magnetic alignment device not including a loading amount measuring unit and a control unit was used. At this time, the separation distance between the first magnet row (including 5 to 20 unit magnets) of the first magnet unit and the second magnet row (including 5 to 20 unit magnets) of the second magnet unit was adjusted to 30 mm.

[0124] <Experimental Example: Evaluation of Alignment Uniformity of Carbon-Based Negative Electrode Active Material> The following experiment was carried out to evaluate the uniformity of alignment of the carbon-based negative electrode active material as the performance of the magnetic alignment device according to the present invention.

[0125] Specifically, in each negative electrode manufactured in the examples and comparative examples, i) the average loading amount of the negative electrode slurry was 200 mg / 25 cm 2 The first unit area (10 cm × 10 cm) in the casting area and ii) the average loading amount of the negative electrode slurry is 400 mg / 25 cm 2A second unit area (10 cm x 10 cm) was arbitrarily set within the casting area.

[0126] Thereafter, X-ray diffraction spectroscopy (XRD) and near-edge X-ray fluorescence spectroscopy (NEXAFS) were performed on three arbitrary points in each of the first and second unit regions to measure the spectra.

[0127] At this time, the measurement conditions for the near-edge X-ray fluorescence spectrometer (NEXAFS) and X-ray diffraction (XRD) are as follows.

[0128] (1) Near-end X-ray fluorescence spectrometer (NEXAFS) - Acceleration voltage: 1.0GeV~1.5GeV - Storage current: 80~350mA - Angle of incidence: 60° or 0°

[0129] (2) X-ray diffraction (XRD) - Target: Cu (Kα-ray) Graphite monochromator - Slit: Divergence slit = 1 degree, Receiving slit = 0.1mm, Scattering slit = 1 degree

[0130] From the spectra measured under the above conditions, i) the average alignment degree (i.e., the average value of the alignment degree at each point) and ii) the error rate between each point and the average alignment degree were calculated for each carbon-based negative electrode active material according to Equation 1 and Equation 2. The results are shown in Table 2.

[0131] [Formula 1] OI=I 004 / I 110

[0132] In formula 1, I 004 indicates the area of ​​the peak representing the (004) crystal plane in the X-ray diffraction spectroscopy (XRD) measurement of the negative electrode active layer, I 110 indicates the area of ​​the peak indicating the (110) crystal plane when the negative electrode active layer is measured by X-ray diffraction spectroscopy (XRD).

[0133] [Formula 2] S 60 / 0 =I60 B / A / I0 B / A

[0134] In formula 2, S 60 / 0 is the peak intensity ratio (I60 B / A ) at an incident angle of 60° (I0 B / A ) value.

[0135] [Table 2]

[0136] As shown in Table 2, the negative electrode manufactured using the magnetic alignment device according to the present invention had a high degree of alignment of the carbon-based negative active material contained in the negative active layer. In addition, it was confirmed that the error rate between the alignment degree at any three points and their average value was low, at 3% or less, in the negative active layer of the manufactured negative electrode. This means that the magnetic alignment device according to the present invention aligns the carbon-based negative active material uniformly on the negative current collector with a high degree of alignment.

[0137] From these results, it can be seen that the magnetic alignment device according to the present invention can align the carbon-based negative electrode active material with high alignment and uniformity relative to the negative electrode current collector by measuring the loading amount of the negative electrode slurry in real time and individually reflecting it to the unit magnets included in the first magnet row of the first magnet unit and the second magnet row of the second magnet unit.

[0138] Although the present invention has been described above with reference to preferred embodiments, it will be understood that a person skilled in the art or having ordinary knowledge in the art may make various modifications and changes to the present invention without departing from the spirit and technical scope of the present invention as described in the claims below.

[0139] Therefore, the technical scope of the present invention is not limited to the contents described in the Summary of the Invention of the specification, but is defined by the claims. [Explanation of symbols]

[0140] 10: Magnetic alignment device 20:Transfer section 30: Coating section (die coater) 110: Loading amount measurement unit 111: First web gauge 112: 2nd web gauge 120a: First magnet section 121a: First distance adjustment means 122a: 1st magnet row 120b: Second magnet part 121b: Second distance adjustment means 122b: Second magnet row 130: Control unit 140:Drying section C: Negative electrode current collector S: Negative electrode slurry

Claims

1. A magnetic alignment device for a negative electrode, which applies a magnetic force to a negative electrode sheet in which a negative electrode slurry containing a carbon-based negative electrode active material is applied onto a negative electrode current collector, thereby orienting the carbon-based negative electrode active material, a first magnet portion and a second magnet portion respectively disposed above and below the traveling electrode sheet; a loading amount measuring unit that is disposed upstream of the first magnet unit and the second magnet unit with respect to a running direction of the electrode sheet and that measures a loading amount of negative electrode slurry disposed on the electrode sheet; a control unit that adjusts a distance between the first magnet unit and the second magnet unit according to a loading amount of the negative electrode slurry measured by the loading amount measurement unit, The first magnet section and the second magnet section each include a plurality of unit magnets arranged in the width direction of the negative electrode slurry, and each unit magnet individually moves up and down in a direction vertical to the running electrode sheet, and the separation distance between the unit magnet and the opposing unit magnet is adjusted around the electrode sheet.

2. 2. The negative electrode magnetic alignment device of claim 1, wherein the control unit includes a database in which a reference interval value between the first magnet unit and the second magnet unit according to a loading amount of the negative electrode slurry is stored, and the control unit calculates a reference interval value corresponding to the loading amount of the negative electrode slurry measured by the loading amount measurement unit to adjust a separation distance between the first magnet unit and the second magnet unit.

3. Each unit magnet provided in the first magnet section and the second magnet section is a support portion which is fixed individually to each unit magnet; 2. The negative electrode magnetic alignment device according to claim 1, further comprising: a distance adjustment means connected to the support and configured to induce an elevation movement of the support in a direction perpendicular to the electrode sheet during movement.

4. 2. The negative electrode magnetic alignment device according to claim 1, wherein the separation distance between the first magnet portion and the second magnet portion is 10 mm to 50 mm.

5. The negative pole magnetic alignment device of claim 1 , wherein the first magnet portion and the second magnet portion include magnets having opposite poles.

6. The apparatus of claim 1 , wherein the loading amount measuring unit includes at least one of a web gauge and an ultrasonic sensor.

7. The ultrasonic sensor includes: an ultrasonic generating unit that scans the surface of the negative electrode slurry with ultrasonic waves; an ultrasonic receiving unit that receives ultrasonic waves returned from the ultrasonic generating unit after the ultrasonic waves have scanned the loaded negative electrode slurry; 7. The negative electrode magnetic alignment device according to claim 6, further comprising: a data transmission unit that calculates a loading amount of the negative electrode slurry from data obtained by scanning and transmits the calculated amount to the control unit.

8. The magnetic alignment device of claim 1 , further comprising a drying unit configured to dry the negative electrode slurry in which the carbon-based negative electrode active material is aligned by the first magnet unit and the second magnet unit.

9. applying a negative electrode slurry including a carbon-based negative electrode active material onto a negative electrode current collector; aligning the carbon-based negative electrode active material contained in the negative electrode slurry by using the negative electrode magnetic alignment device according to claim 1; and drying the negative electrode slurry in which the carbon-based negative electrode active material is aligned to form a negative electrode active layer. The step of aligning the carbon-based negative electrode active material is controlled by adjusting a distance between the negative electrode slurry and a magnet part of the magnetic alignment device according to a loading amount of the negative electrode slurry.

10. The negative electrode slurry is 100 mg / 25 cm 2 ~500mg / 25cm 2 The method for producing a negative electrode according to claim 9 , wherein the coating is carried out at a loading amount of

11. In the negative electrode active layer, the degree of alignment (O.I) of the carbon-based negative electrode active material represented by the following formula 1 is 0.1 to 5.0, [Formula 1] O.I=I 004 / I 110 In Formula 1, I 004 represents the area of ​​the peak representing the (004) crystal plane in X-ray diffraction spectroscopy measurement of the negative electrode active layer, I 110 The method for producing a negative electrode according to claim 9 , wherein R represents the area of ​​a peak indicating a (110) crystal plane in X-ray diffraction spectroscopy of the negative electrode active layer.

Citation Information

Patent Citations

  • Graphite powder and nonaqueous electrolyte secondary battery

    JP2006083030A

  • Method and device for applying a magnetic field to an article

    JP2019534155A

  • Basis weight measuring device and electrode manufacturing method

    JP2021081347A

  • Electrode manufacturing method and electrode paste coating device

    JP2022080610A

  • Process for manufacture of lithium ion secondary battery

    WO2012077177A1